2017
DOI: 10.1002/smll.201702691
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous pH‐Dependent Nanofluidic Salinity Gradient Power

Abstract: Previous studies on nanofluidic salinity gradient power (NSGP), where energy associated with the salinity gradient can be harvested with ion-selective nanopores, all suggest that nanofluidic devices having higher surface charge density should have higher performance, including osmotic power and conversion efficiency. In this manuscript, this viewpoint is challenged and anomalous counterintuitive pH-dependent NSGP behaviors are reported. For example, with equal pH deviation from its isoelectric point (IEP), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 37 publications
1
71
0
Order By: Relevance
“…The device demonstrated rapid consumption of fluorescent dye samples and can be used as an effective microfluidic concentrator for fluorescent dyes to achieve a 60‐fold concentration enrichment in 200 s. Yeh et al . revealed an abnormal counterintuitive pH‐dependent nanofluid salinity gradient power (NSGP) behaviour . Their results showed that at a concentration of 1000, the conversion efficiency of a single alumina nanopore reacheed 26.3% at pH 3.5, which can produce a maximum osmotic power density of up to 5.85 kW m −2 .…”
Section: Applications Of Ion Transport Based On Icpmentioning
confidence: 99%
“…The device demonstrated rapid consumption of fluorescent dye samples and can be used as an effective microfluidic concentrator for fluorescent dyes to achieve a 60‐fold concentration enrichment in 200 s. Yeh et al . revealed an abnormal counterintuitive pH‐dependent nanofluid salinity gradient power (NSGP) behaviour . Their results showed that at a concentration of 1000, the conversion efficiency of a single alumina nanopore reacheed 26.3% at pH 3.5, which can produce a maximum osmotic power density of up to 5.85 kW m −2 .…”
Section: Applications Of Ion Transport Based On Icpmentioning
confidence: 99%
“…In this case, the osmotic current is estimated as . On the other hand, the osmotic voltage can be obtained by letting [ 44 ]. Figure 4 a illustrates the simulated current–voltage and the power density–voltage curves of the considered mesopore system in 1000 mM/1 mM salinity gradient where the power density is calculated as .…”
Section: Resultsmentioning
confidence: 99%
“…This can be attributed to the significant ICP effect arising from the high space charge density of a PE layer [ 48 ]. Hence, we calculate the maximum osmotic power density ( ) as the highest value of the P–V curve in the present manuscript, instead of using the simple formula that the previous studies adopted [ 44 , 63 , 64 ], …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations